Micro-Optics for Lab-on-a-Chip - Figurova, Maria; Gaso, Peter; Pudis, Dusan (Communications - Scientific letters of the University of Zilina, 2017)
Lab-on-a-chip (LOC) is nowadays one of the most interesting topics at the field of biomedicine and biosensing applications. Mainly devices that integrate a detection system right into a chip with microfluidic network are highly desirable. In this article we will present Mach-Zehnder interferometer created in IP-Dip photoresist by direct laser lithography system for laboratory on chip applications. Interferometer will be later used for biosensing application as integrated micro-optical device inside a microfluidic chip. Measurements of transmission characteristics of water solution with different sugar concentration show promising ability of the Mach-Zehnder interferometer to detect different liquids on principle of refractive index change.